Cuidados de enfermería y su relación con la incidencia de úlceras por presión en adultos mayores internados en el Hospital Abel Gilbert Pontón. Noviembre 2023 - abril 2024. - Lara Álava, Jair José (2024)
The incidence of pressure ulcers despite scientific evidence contributes to continued research to improve the care and treatment of these by nursing staff. Pressure ulcers are defined as lesions that compromise the integumentary integrity, developing damage to the skin, causing alterations in deep tissues. Aim: To analyze nursing care and its relationship with the incidence of pressure ulcers in older adults admitted to the Abel Gilbert Pontón Hospital during the period from November 2023 to April 2024. Methodology: A mixed approach that integrates quantitative approaches is used. and qualitative. The quantitative modality will be used to analyze numerical data on the incidence of pressure ulcers and care practices carried out by staff. The total population consisted of 84 elderly patients receiving care and 80 members of the nursing staff who work in the Abel Gilbert Pontón Hospital. Results: An incidence of 17% was obtained, most cases occurred in male patients, in the range of 65 to 75 years. It was also found that 3 cases were grade II PUs and 11 grade I. Likewise, it was found that the majority of nursing interventions are being carried out appropriately.